IMPLEMENTASI KEBIJAKAN PELAYANAN PENUMPANG ANGKUTAN PELABUHAN PENYEBERANGAN SUNGAI SELARI-AIR PUTIH KABUPATEN BENGKALIS TAHUN 2023 - Zikri, Muhammad Al; ', isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Rapid developments in maritime transportation have increased the number of people traveling and transporting goods between regions. To balance this increase, transportation providers need to provide a service with optimal value intended for passengers and goods. A number of regulations have been implemented, including "Regulation of the Minister of Transportation of the Republic of Indonesia Number PM. 39 of 2015 concerning Standards for Ferry Transport Passenger Services. Passengers are individuals who use transportation, such as planes, trains, buses, or other types of transportation. At the Selari River Crossing Port in Bengkalis Regency, Riau Province, which serves the Air Putih - Selari River route, there is congestion, especially on weekends when people choose to make the crossing to Bengkalis Island. Passenger services at this port should meet service standards regulated by statutory regulations so that port activities can run well.lari Crossing Port UPT, Bengkalis Regency. The data used in this research is divided into two types, namely primary data collected through purposive informant selection techniques, and secondary data in the form of supporting information related to passenger services. Data collection techniques involve interviews and documentation. The data analysis was carried out using qualitative analysis methods.The results of this research indicate that the implementation of the 2023 Selari-Air Putih River Crossing Harbor Passenger Transport Service Policy in Bengkalis Regency has not gone well and, there are still several service aspects that need to be improved and improved further. However, in reality there are several aspects of service to passengers whose categories do not comply with applicable regulations. The research approach that was chosen was a qualitative approach with the type of research being descriptive. This research was carried out at "UPT White Water-Sungai Selari Crossing Port, Bengkalis Regency". The data used in the scope of this research is divided into two types, namely primary data which is collected using purposive informant selection techniques, and secondary data in the form of supporting information related to passenger services. Data collection techniques involve two things, namely interviews and documentation. The data analysis was carried out using qualitative analysis methods. The results of this research provide an indication that the implementation of the 2023 Selari-Air Putih River Crossing Harbor Passenger Transport Service Policy in Bengkalis Regency has not gone well and, there are still several service aspects that need to be improved and improved further. Keyword: Service Quality, Service Standards, Transportation.